Alcohol consumption among residents of the Olga Benário Rural Settlement, Central Brazil - da Silva, Andrécia Cósmen; Silva Vargas, Lorena; Chaveiro Moraes, Rayrane Clarah; Lucchese, Roselma; Vera, Ivania; Alves Guimarães, Rafael; de Castro, Paulo Alexandre; Duarte Gregório, Valéria (O Mundo da Saúde, 2017)
The high consumption of alcoholic beverages is a public health problem and focuses on some vulnerable populations, such as residents of rural settlements. A cross-sectional study population-based investigating the alcohol consumption in 172 individuals. The objective was to estimate the prevalence and factors associated with alcohol consumption among residents of the Olga Benário Rural Settlement, located in the municipality of Ipameri in the southeastern region of the state of Goiás. The data were collected through a structured questionnaire and screening instrument titled Alcohol, Smoking and Substance Involvement Screening Test (ASSIST). The results showed prevalence of alcohol use in the life of 77.9%, the last three months and 29.1% for the last month of 19.2%. In multivariate analysis the independent factor associated with the consumption of alcohol was male. Regarding the use of alcohol in the last three months we have been associated income > 1000.00 reais, evangelical religion and marijuana use. Associated with the last month of consumption was obtained evangelical religion. Of the total number of participants, 20.14% presented harmful use of alcohol, where it was found in a multivariate analysis that the evangelical religion, the Catholic religion, having suffered violence and marijuana use remained independent factors of the harmful use of alcohol. The variable evangelical religion appeared as a protective factor against alcohol. The knowledge of these variables directs the planning of actions of health promotion aimed at the prevention of alcohol use and improvement of the quality of life of rural settlers.